(untitled) (Biological Sciences - PJSIR, 2006)
Anticonvulsant effect of the leaf extracts of Emilia sonchifolia is reported for the first time. The ethanol, chloroform and aqueous extracts, especially the aqueous extract, showed marked anticonvulsant effect (ED50 of 4 mg/ kg and 8 mg/kg in chicks and mice, respectively). This research finding gives scientific justification to the traditional healers in Nigeria for the use of aqueous leaf extract of the plant for treating infantile convulsion. The extracts of E. sonchifolia showed concentration-dependant protective effect against maximal electroshock (MES) and strychnine- induced seizures (SIS). The potent anticonvulsant effect exhibited by the extracts of E. sonchifolia (especially the aqueous extract) is an indication of its promising anticonvulsant application as a possible new clinical drug. Further studies on the principal anticonvulsant compounds of the aqueous extract are in progress.